A genome-wide distribution of 8-oxoguanine correlates with the preferred regions for recombination and single nucleotide polymorphism in the human genome - Ohno, Mizuki; Miura, Tomofumi; Furuichi, Masato; Tominaga, Yohei; Tsuchimoto, Daisuke; Sakumi, Kunihiko; Nakabeppu, Yusaku (Genome Research, 2006)
8-Oxoguanine (8-oxoG), a major spontaneous form of oxidative DNA damage, is considered to be a natural cause of genomic diversity in organisms because of its mutagenic potential. The steady-state level of 8-oxoG in the nuclear genome of a human cell has been estimated to be several residues per 106 guanines. In the present study, to clarify the genome-wide distribution of 8-oxoG in the steady state, we performed fluorescence in situ detection of 8-oxoG on human metaphase chromosomes using a monoclonal antibody. Multiple dot-like signals were observed on each metaphase chromosome. We then mapped the position of the signal at megabase resolution referring to the cytogenetically identified chromosomal band, and demonstrated that 8-oxoG is unevenly distributed in the normal human genome and that the distribution pattern is conserved among different individuals. Moreover, we found that regions with a high frequency of recombination and single nucleotide polymorphisms (SNPs) are preferentially located within chromosomal regions with a high density of 8-oxoG. Our findings suggest that 8-oxoG is one of the main causes of frequent recombinations and SNPs in the human genome, which largely contribute to the genomic diversity in human beings.